Optimal bilayer composites for temperature-tracking wireless electronics - Kim, Doyoung; Kim, Wooseok; Kim, Jihwan; Lee, Hee Kyu; Joo, Janghoon; Kim, Bogeun; Allen, Mark G.; Lu, Dengyang; Venkatesh, Vishal; Huang, Yanghang; Yu, Ki Jun; Park, Young Jin; et al. (Nanoscale, 2024)
Modern silicone-based epidermal electronics engineered for body temperature sensing represent a pivotal development in the quest for advancing preventive medicine and enhancing post-surgical monitoring. While these compact and highly flexible electronics empower real-time monitoring in dynamic environments, a noteworthy limitation is the challenge in regulating the infiltration or obstruction of heat from the external environment into the surface layers of these electronics. The study presents a cost-effective temperature sensing solution by embedding wireless electronics in a multi-layered elastomeric composite to meet the dual needs of enhanced thermal insulation for encapsulation in contact with air and improved thermal conductivity for the substrate in contact with the skin. The encapsulating composite benefits from the inclusion of hollow silica microspheres, which reduce the thermal conductivity by 40%, while non-spherical aluminum nitride enhances the thermal conductivity of the substrate by 370%. The addition of particles to the respective composites inevitably leads to an increase in modulus. Two composite elements are engineered to coexist while maintaining a matching low modulus of 3.4 MPa and a stretchability exceeding 30%, all without compromising the optimized thermal properties. Consecutive thermal, electrical, and mechanical characterization confirms the sensor's capacity for precise body temperature monitoring during a single day's lifespan, while also assessing the influence of behavioral factors on body temperature.
Keywords: Bilayer composites; Body temperature; Cost effective; Dynamic environments; External environments; Preventive medicines; Real time monitoring; Surface layers; Temperature sensing; Temperature tracking